2018
DOI: 10.1016/j.vprsr.2018.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, risk factors and molecular characterization of Cryptosporidium infection in cattle in Addis Ababa and its environs, Ethiopia

Abstract: A cross-sectional study was conducted to determine the prevalence and risk factors of Cryptosporidium infection and identify species of the parasite in cattle in central Ethiopia. Faecal samples, collected from 392 dairy cattle managed under intensive and extensive production system, were analyzed by the Modified Ziehl-Neelsen (MZN) microscopy, Nested PCR, PCR-RFLP and sequence analyses of the SSU rRNA gene of Cryptosporidium. The overall prevalence, the prevalence in the extensive and intensive farms was 18.6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
21
2
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 46 publications
4
21
2
6
Order By: Relevance
“…In the Ogun state of Nigeria, one study involving the detection of Cryptosporidium coproantigens recorded a higher prevalence of 37.5% [ 27 ] than the present study. The prevalence rate for the current study was however higher than a similar study in Addis Ababa, Ethiopia, which reported a rate of 18.6% using both modified Ziehl-Neelsen staining and molecular techniques [ 22 ]. A study in Aizawl district in India using both modified Ziehl-Neelsen and molecular detection [ 35 ] and one other in Malaysia peninsular using only molecular detection method for Cryptosporidium [ 15 ] also recorded rates of 13% and 12.5%, respectively, which were lower compared to the present study.…”
Section: Discussioncontrasting
confidence: 76%
See 2 more Smart Citations
“…In the Ogun state of Nigeria, one study involving the detection of Cryptosporidium coproantigens recorded a higher prevalence of 37.5% [ 27 ] than the present study. The prevalence rate for the current study was however higher than a similar study in Addis Ababa, Ethiopia, which reported a rate of 18.6% using both modified Ziehl-Neelsen staining and molecular techniques [ 22 ]. A study in Aizawl district in India using both modified Ziehl-Neelsen and molecular detection [ 35 ] and one other in Malaysia peninsular using only molecular detection method for Cryptosporidium [ 15 ] also recorded rates of 13% and 12.5%, respectively, which were lower compared to the present study.…”
Section: Discussioncontrasting
confidence: 76%
“…There are many reports of Cryptosporidium infections in livestock such as cattle worldwide [ 22 25 ]. In neighbouring Nigeria in the West African region, several studies of Cryptosporidium infections in cattle have been conducted [ 26 – 28 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding was comparable with the results of Benhouda et al (15) whom recorded infection rate 40% in young calves in Algeria and the 35.5% were recorded in diarrheic calves in Sudan (16). However, the prevalence was higher than the 14.4% infection prevalence reported from dairy farms in the Qinghai-Tibetan Plateau Area in China (7), 17.0% reported from cattle tested in Poland (17) and 18.6% in cattle in Ethiopia (18). On the other hand, the infection rate was lower than the 42.85% reported in calves in Kut city (19), 47.68% in pre-weaned dairy calves in Northeastern China (3) and 52.2% in neonatal calves in Algeria (20).…”
Section: Discussionsupporting
confidence: 87%
“…Infection of Cryptosporidium spp. causes inflammation in the mucosal tissues, associated with great numbers of macrophages and neutrophils in the infected tissue (9). Diagnosis of Cryptosporidium spp.…”
Section: Introductionmentioning
confidence: 99%